Does the Association Between Fatigue and Fatigue Self-management Preference Vary by Breast Cancer Stage?. Issue 1 (January 2022) - Jang, Min Kyeong; Park, Chang; Lee, Keon Suk; Lee, KyungHi; Hwang, Eun Kyung; Joh, Hye Jin; Lim, Kyung Hee; Ko, Yun Hee; Kim, Dong Mi; Han, Jeehee; Kim, Sue
Abstract : Background: Cancer-related fatigue (CRF) is a major issue facing breast cancer survivors (BCS) that can negatively impact their symptoms and quality of life. Objectives: The aims of this study were to examine levels of fatigue, identify preferred types of fatigue self-management, and explore the relationship between fatigue levels and management choices by cancer stage. Methods: This cross-sectional descriptive study included 229 BCS recruited from 5 hospitals in Korea. The study inclusion criteria were limited to BCS between 20 and 69 years old in stages 1, 2, or 3 who were undergoing or had completed active therapy. The Revised Piper Fatigue Scale and a questionnaire developed for fatigue management were used for data collection. Results: The stage 2 group experienced more fatigue (mean, 5.31) than the other cancer stage groups, and significant differences in fatigue were found between stages 1 and 2 ( P < .001). Fatigue self-management choices showed different correlations with fatigue levels in each stage. Physical activity control was most frequently used in stage 1, whereas exercise was most frequently used in stages 2 and 3. Multivariate regression analysis showed that exercise consistently and effectively decreased all fatigue dimensions. Conclusion: Stage 2 BCS experienced the greatest level of CRF, and fatigue levels and management choices differed in BCS by cancer stage. Implications for Practice: Recognizing how CRF and patients' preferences for fatigue self-management may differ by cancer stage can alert clinicians in assessing CRF and tailoring effective fatigue management for BCS.